Engineered seabed sediment via microwave-assisted Ni²⁺ substitution as a catalyst for double-stage pyrolysis of plastic waste: A novel approach to methane reforming and enhanced hydrogen production - Sobri Sobri; Widya Wijayanti; Nurkholis Hamidi; Purnami; Willy Satrio Nugroho; I.N.G. Wardana (Results in Engineering)
This study engineered seabed sediment with microwave-assisted Ni2+-substitution to enhance its composition and properties. The catalytic activity of microwave-assisted Ni2+-substituted seabed sediment (Mwx%Ni-SB) was investigated in the two-stage pyrolysis of plastic waste for hydrogen production. The characterization reveals microwave irradiation synergistically modifies the physical properties (increasing functional groups, reducing crystallinity) and electronic properties (modulating bandgap energy, increasing electron density) of the Mwx%Ni-SB, thereby improving methane reforming performance. Microwave treatment compresses and rearranges Ni2+ ions within the sediment lattice, resulting in increased order and density, and creating defects that enhance catalytic activity. GC-TCD analysis demonstrates that the use of catalysts in the first and second stages more than doubled hydrogen production (109.74 %) compared to not using catalysts. Therefore, increased Ni2+ substitution significantly reduced methane production by 49.04 % while simultaneously boosting hydrogen production by 23.00 %.